Labeling efficiency of Tb3+ conjugated CD133 monoclonal antibody nanocomplex targeting in vitro metastatic cancer cells - Nhat Minh, Le; Trong Nhan, Vo; Thu Huong, Tran; Thi Nga, Nguyen; Tri Vien, Le; Thi Kim Hue, Phung (Vietnam Journal of Biotechnology, 2020)
Efficient cancer treatment remains a huge challenge worldwide. As reported by the World Health Organization, the number of cancer patients is estimated to be 24 million in 2035, which is a 70% increase compared to 14.1 million in 2012. The severity of cancer is due to the presence of cancer stem cells (CSCs), which are directly related to drug resistance, metastasis, and tumor relapse. Because of the unknown location of the primary tumor and/or the residency of CSCs, standard therapies deliver a high dose of drugs to the whole body, which can have negative effects and deadly consequences for patients undergoing treatment. Therefore, efficient luminescent materials for labeling and tracking CSCs are urgently needed to determine their distribution and target treatment. Herein, a fluorescent Tb3+ nano-ion and CD133 monoclonal antibody (mAb) were conjugated into a nano probe-complex (ET2). Tb3+ nano-ion is a rare-earth element and the CD133 mAb targets CD133, which is a CSC surface marker. The Tb3+ nanorods were surface treated with silica and activated with -NH2 for functioning before being coupled with CD133 mAb. Strong fluorescent Tb3+ nanorods were used to decrease the toxicity of high-dose medicines, and the purpose of the CD133 mAb was to increase the specific binding capacity of CSCs to the ET2 nanocomplex. The luminescent properties of this coupled ET2 complex were determined and its ability to target and label CSCs was determined using the pluripotent human embryonic carcinoma cell line, NTERA-2. Fluorescence microscopy showed strong luminescent signals from ET2-exposed NTERA-2 cells. It was also demonstrated that the ET2 nanocomplex effectively labeled up to 97.74% of the tested NTERA- 2 cells, but only 2.35% of CCD-18Co human colon normal cells. Therefore, these results show that the ET2 luminescent nanocomplex specifically targeted and labeled CSCs, and may be used for further applications in fundamental and clinical research.